Effectiveness of Computer-based Instructional Package in Educational Psychology with Respect to Various Determinants - Chaudhary, Sarita; TyaGi, s.k. (JOURNAL OF INDIAN EDUCATION, 2021)
This study was related to two broad areas namely— Information and Communication Technology, and Educational Psychology. In the present study, the investigator has attempted to find out the effectiveness of computerbased instructional package on the pupil teachers’ achievement in educational psychology, with respect to various psycho-social determinants. This study was an attempt to explore the possibilities of applying computer-based instruction for teachers’ training programme. In the present research, the investigator has developed Computer-Based Instructional Package in Educational Psychology and assessed the effectiveness of the package, in terms of achievement in the educational psychology of the pupil teachers. The pre-test-post-test control group design has been used for the experiment.